Fast fashion e as armadilhas do discurso democrático: análise da rede de varejo Riachuelo - Brunini, Nathália Cristina (2018)
The theme of this research is the fashion market model known as fast fashion, characterized by its rapid production and marketing speed. The study seeks to understand this model as an ambivalent system, in other words, on the one hand, the "democratization" of fashion. On the other hand, a predatory and exploitative circuit, since it increases the access of the general public to the latest trends due to the affordable price, but at the same time expands the political, economic and social cracks, explained by the precarious conditions of work in which it is manufactured part of the fast fashion products. The central hypothesis is that the partnerships made between renowned designers and sizeable fast fashion retailers are a symptom of the new modes of communication, in an era marked by the generalization of aesthetic strategies, with a commercial purpose, under the discourse of accessibility to the general public. As a corpus of the research, we opted for the case study of the Riachuelo retail chain, especially the partnerships signed between the Brazilian company and four renowned designers: Oskar Metsavaht (2010), Osklen, Donatella Versace (2014), Versace, Karl Lagerfeld (2016), Chanel and Fendi, and one of the most recent, Paula Raia (2017), self-styled slow fashion. As methodological strategies, we follow the proposal to broadly contextualize the incidence of fast fashion in the major European fashion centres and at Brazil; to analyse the growth and repositioning of Riachuelo, which, from a small fabric store in Pernambuco (the 1940s), became a Brazilian fashion retail giant; and to discuss, conceptually, the fragility of this democratization within the framework of fast fashion, based on the explication of Riachuelo's communicational strategies, present in materials for the partnerships as mentioned above